Pemanfaatan E-Modul Berbasis Canva terhadap Hasil Belajar Kognitif Peserta Didik Di SMAN 61 Jakarta - Ayuning Tyas, Triesna; Sofyan Hardi, Ode; Setiawan, Cahyadi (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
The purpose of this study was to determine the effect of utilizing Canva-based e-module teaching materials on the cognitive learning outcomes of class X students on the material of lithospheric dynamics at SMA Negeri 61 Jakarta. The nonequivalent control group design method was used in this quasi-experimental study. In this study, purposive sampling technique was used with the sample used, namely class X-7 as an experimental class that utilized the application of Canva-based e-modules during the learning process and X-8 as a control class that did not use Canva-based e-modules in learning. Based on the results of research in the field, a significant effect was obtained on the learning outcomes of experimental class students. The learning outcomes of the experimental class experienced a high increase to 88.64 from 49.92. While the control class learning outcomes increased to 83.56 from 51.36. The acquisition of the Sig. value in the t test (Independent sample t-test) of 0.046 which means H0 is rejected and Ha is accepted, because the Sig value. <0.05 is reinforcing evidence of the discovery of differences in students' cognitive learning outcomes. Therefore, there is a significant effect in improving the cognitive learning outcomes of class X students at SMA Negeri 61 Jakarta after utilizing Canva-based E-module teaching materials in learning geography material on the dynamics of the lithosphere